Innovative Curriculum: Creative Systems Thinking and Humanized Healthcare in a Multicultural Society toward creating Innovation in the areas of Healthcare and Public Health Services, Boromarajchanok Institute, Ministry of Public Health - จูฑะรสก มกราพันธุ์; อมรโรจน์วรวุฒิ วัชรี; เจริญสุข ศุกร์ใจ; ทิพยผลาผลกุล เบญจพร; จูฑะรสก อณิษฐา (Journal of Health Science of Thailand, 2021)
This research was conducted based on a documentary analysis. Its purpose was to study the innovative curricum development that emphasized creative systems thinking and humanized health care in a multicultural society. The lessons learned were drawn from knowledge management document of two innovative integrated learning models: (1) “Simulated Family System and its humanistic learning process” and (2) “One College One Community model”, including the experimental outcomes of the two innovation models that were implemented in educational institutes during 2008 – 2019. The input data covered research projects, academic journal and empirical data using the connoisseurship technique. The findings highlighted five curriculum strategies as the key driving factors: (1) open learning space, (2) create hands-on learning platform, (3) find networking partner, (4) adopt routine-to-research learning approach, and (5) build trust and competence with local communities nearby through academic network. The continuous learning approach was the final innovative outcome taking place within the circle of academic institutes, healthcare services facilities and local community. This new curriculum development led to the collaborative learning culture known as “a continuous professional development” among academic staff, healthcare practitioners and local people.